Psychometric Properties of the Filipino Version of Harris-Hip Score Among Patients with Osteoarthritis and Hip Fractures - Diovince Tan; Byron Angeles; Carmelo Braganza; Carlo Fernandez (Philippine Journal of Orthopaedics)
Background: The Harris Hip Score (HHS) is a widely used instrument for assessing hip function and quality of life in patients with hip conditions. However, the questionnaire has not been validated in Filipino, limiting its use in the Philippines. This study aimed to translate, culturally adapt, and validate the HHS for Filipino-speaking patients with osteoarthritis or hip fractures to enhance its clinical and research applicability.